BIODECOLORIZATION OF TEXTILE INDUSTRIAL WASTE BY THERMOPHILIC BACTERIA Anoxybacillus rupiensis TS04 AND Anoxybacillus flavithermus TS15 - Muharni, Muharni; Yohandini, Heni; Rivai, M Yunus (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2018)
Wastewater of textile industries contained a high content of synthetic dyes that could damage the aquatic ecosystem and environmental aesthetics. The use of microorganisms on the biodecolorization of textile industrial waste had advantages such as low cost and environmentally friendly. The purpose of the study was to determine biodecolorization capability of Anoxybacillus rupiensis TS04 and Anoxybacillus flavithermus TS15 for industrial waste of tie-dye fabrics. Completely randomized design with factorial pattern was used in the research; factor I and II were concentrations of wastewater and types of bacteria, respectively Anoxybacillus rupiensis TS04 showed the highest decolorization ability by 83.25% for wastewater concentration of 80% (v/v) and Anoxybacillus flavithermus TS15 by 69% at 40% (v/v) waste concentration.The highest cell number of Anoxybacillus rupiensis TS04 was obtained as 1.52 x 106 cfu/mL and biodecolorization, textile industrial waste, thermophilic bacteria,Anoxybacillus flavithermusÂ TS15 3.70 x 105cfu/mL.